PEMANFAATAN EKSTRAK BIJI TREMBESI (SAMANEA SAMAN) SEBAGAI KOAGULAN DALAM MENURUNKAN KONSENTRASI PADATAN TERSUSPENSI, DAN ZAT ORGANIK LIMBAH CAIR TAHU - Iva Rustanti Eri; Oktafia Putri W; Marlik Marlik (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Tofu industry is an industry that emits wastewater that can pollute water bodies. Tofu liquid waste comes from soybean soaking water and soybean steaming water, which is still discharged directly in waters such as rivers. Alternative treatment of tofu liquid waste before being discharged into the water needs to be done in order to reduce water pollution, one of which is coagulation-flocculation by utilizing natural materials as coagulants. Natural coagulants or bio-coagulants can be made from trembesi seed (Samanea saman). This study aimed to analyze the biokoagulant of trembesi seed extract in reducing the concentration of suspended solids and organic wastewater in the tofu industry. This research was analytic using Pretest-Posttest Only Control Group Design. The object of this research is tofu wastewater. The method used in this study was coagulation flocculation. The parameters examined were the concentration of suspended solids, organ substances measured as COD, and BOD, on variations in the addition dose of tamarind seed extract. The results of this study indicated that the biokoagulant from trembesi seed extract could reduce the concentration of suspended solids and organic substances in the wastewater of tofu industry, with the most effective dose was 200 ml / L and percentage of removal of SS, COD and BOD respectively of 83.79%, 79.55%, and 87.54%.